Sistem Penjualan Tunai Dan Kredit Property Di PT Sanggraha Property - Asep Ririh Riswaya (STMIK Mardira Indonesia, Bandung, 2013)
The purpose of the study was analyzing accounting information systems sales in the PT Sanggraha Property. Writing method in this study uses qualitative research by using two types of data namely primary and secondary data. Taking technique used is the method of observation, interview and documentation. In this study was using a qualitative descriptive data analysis, which describes the accounting information systems sales to PT Sanggraha Property. The results of this study are expected to provide information regarding the accounting information system sales in the PT Sanggraha Property. That was helping the company to manage the system with better sales and in line with expectations. The conclusion of this study isthey must improve sales accounting information system applied in order to have a good systems and alsohave a policies and authorization in payment process. Keywords: information systems , sales information systems